Nationwide analysis of antimicrobial resistance in pathogenic Escherichia coli strains isolated from diseased swine over 29 years in Japan - Kusumoto, Masahiro; Tamamura-Andoh, Yukino; Hikoda-Kogiku, Yuna; Magome, Asami; Okuhama, Erina; Sato, Keisuke; Mizuno, Yoshino; Arai, Nobuo; Watanabe-Yanai, Ayako; Iwata, Taketoshi; Ogura, Yoshitoshi; Gotoh, Yasuhiro; et al. (Frontiers in Microbiology, 2023)
Pathogenic Escherichia coli strains are important causes of several swine diseases that result in significant economic losses worldwide. In Japan, the use of antimicrobials in swine is much higher than that in other farm animals every year. Antimicrobial resistance in pathogenic E. coli strains also heavily impacts the swine industry due to the limited treatment options and an increase in the potential risk of the One Health crisis. In 2016, we investigated 684 Japanese isolates of swine pathogenic E. coli belonging to four major serogroups and reported the emergence and increase in the highly multidrug-resistant serogroups O116 and OSB9 and the appearance of colistin-resistant strains. In the present study, by expanding our previous analysis, we determined the serotypes and antimicrobial resistance of 1,708 E. coli strains isolated from diseased swine between 1991 and 2019 in Japan and found recent increases in the prevalences of multidrug-resistant strains and minor serogroup strains. Among the antimicrobials examined in this study that have been approved for animal use, a third-generation cephalosporin was found to be effective against the most isolates (resistance rate: 1.2%) but not against highly multidrug-resistant strains. We also analyzed the susceptibilities of the 1,708 isolates to apramycin and bicozamycin, both which are available for treating swine in Japan, and found that the rates of resistance to apramycin and bicozamycin were low (6.7% and 5.8%, respectively), and both antimicrobials are more effective (resistance rates: 2.7% and 5.4%, respectively) than third-generation cephalosporins (resistance rate: 16.2%) against highly multidrug-resistant strains.